ANALISA CRACK IMPELLER PADA CIRCULATING WATER PUMP (CWP) PLTU PAITON 9 DI PT PLN NUSANTARA POWER UMRO GRESIK - Muhammad Indra Setyawan; Rilo Chandra Muhamadin (ENIGMA: Engineering in Green Machinery, 2026)
This internship was conducted with the objective of analyzing the causes of cracking failure on the impeller of the Circulating Water Pump (CWP) at PLTU Paiton 9. The CWP plays a vital role in the power plant cooling system by maintaining turbine thermal efficiency. Impeller failure can significantly reduce condenser performance and cause operational instability. The study was carried out through field observation and laboratory analysis, including X-Ray Fluorescence (XRF) for material composition, hardness testing, penetrant test, and micrographic examination on stainless steel 316 material. The results showed that the impeller had an average hardness value of 91.9 HRB with chemical composition meeting the standard specifications. However, porosity and microcracks were observed, mainly due to residual stress and chloride ion corrosion from seawater exposure. Microstructural analysis revealed chromium carbide (Cr₂₃C₆) precipitation along grain boundaries, indicating sensitization and reduced intergranular corrosion resistance. It was concluded that the main causes of impeller cracking were the combined effects of corrosion, welding-induced thermal stress, and extreme operational conditions. Recommendations include optimizing GTAW welding parameters, performing regular preventive maintenance, and improving operational control to extend impeller service life and enhance system reliability.